Sphingosine-1-phosphate affects myocardial vascular homeostasis by regulating the balance of sphingosine-1-phosphate receptors in the hearts of diabetic mice - Guozhu Jin; Hu Zhao; Lun Li; Qian Cao; Hui Yan (Journal of International Medical Research)
Objective This study aimed to explore the effect of sphingosine-1-phosphate on vascular homeostasis in the myocardium of diabetic mice. Methods Bioinformatics analyses were performed to analyze the targets and function of sphingosine-1-phosphate in diabetes. C57BL/6 mice were used to establish diabetic models and treated with sphingosine-1-phosphate. Pathological examination was used to evaluate the damage to the myocardium. Immunohistochemistry and western blot analyses were used to examine the expression of molecules involved in vascular function and sphingosine-1-phosphate receptors. Endothelial nitric oxide synthase level was detected via enzyme-linked immunosorbent assay. Results Multiple Gene Ontology entries of sphingosine-1-phosphate were associated with vascular homeostasis. Blood glucose level, food intake, and water intake increased and body weight decreased in diabetic mice, whereas these changes were relieved in the sphingosine-1-phosphate group. Sphingosine-1-phosphate alleviated the myocardial injury and restored the expression levels of vascular endothelial-cadherin, vascular endothelial growth factor, and CD31 in the myocardium of diabetic mice to some extent. The serum level of endothelial nitric oxide synthase increased in the sphingosine-1-phosphate group. Additionally, sphingosine-1-phosphate was demonstrated to act on its receptors S1PR1, S1PR2, and S1PR3, which were downregulated in the myocardium of diabetic mice and significantly upregulated after sphingosine-1-phosphate treatment. Conclusion Sphingosine-1-phosphate may restore myocardial vascular homeostasis by regulating the balance of sphingosine-1-phosphate receptors in diabetic mice, suggesting sphingosine-1-phosphate/sphingosine-1-phosphate receptors as potential therapeutic targets for diabetic myocardial injury.